The servant leader : how to build a creative team, develop great morale, and improve bottom-line performance - Autry, James A. (New York : Crown Business, 2001)
Annotation A Practical Guide to Using the Principles of Servant Leadership Leadership is a calling. And servant leadership--the idea that managing with respect, honesty, love, and spirituality empowers employees--helps individuals answer that calling. Bestselling author and former Fortune 500 executive James A. Autry reveals the servant leader's tools, a set of skills and ideals that will transform the way business is done. It helps leaders nurture the needs and goals of those who look to them for leadership. The result is a more productive, successful, and happier organization, and a more meaningful life for the leader. Autry reveals how to remain true to the servant leadership model when handling day-to-day and long-term management situations, including how to: -Provide guidance during conflict and crisis -Assure your continued growth and progress as a leader -Train managers in the principles of servant leadership -Transform a company with morale problems into a great place to work Practiced by one-third of the companies on Fortune's "100 Best Companies to Work For" list, servant leadership is a thriving philosophy. Ultimately, Autry explores how it can be a valuable, refreshing, and rewarding approach to leading others in business life. "When I first read Jim's work, I was thrilled. Finally, someone had clearly and con-cisely articulated these principles in a way that people can quickly adopt into their lives."--from the foreword by Howard Behar, retired president, Starbucks "This is an awesome book. James Autry's gift is that he brings lofty ideals down to earth with general illustrations that make them easy to understand and apply. I highly recommend it!"--JackCanfield, coauthor, "Chicken Soup for the Soul "The Servant Leader describes the kind of leadership upon which Starbucks Coffee Company has been built and is a concept that is closely aligned with our mission and guidin.
Annotation "In a time when the business world seems rife with corporate scandals, many executives and managers are turning to ""servant leadership,"" a business movement that places ethics and responsibility at the center of organizational life. In The Servant Leader, James A. Autry-author, former Fortune 500 executive, and consultant-shows how the servant leadership model can be applied to both day-to-day and long-term business operations. With a practical analysis of the challenges facing businesses, The Servant Leader shows how to lead with honesty and respect in an uncertain environment, beginning with a commitment to inspire the best in others."
A foundation of character and vision. Characteristics of the leader as servant ; Understanding the three aspects of vision -- Servant leader as manager: the everyday nuts and bolts. Finding the right people ; Training the servant leader ; The tools of the trade ; Coping with the high-tech workplace -- The harsh realities of organizational life. Organizational issues ; Personal issues ; Legal issues -- Finding the balance. Servant leadership and the crisis of loyalty ; Conflict ; The responsibilities of family and community life ; Leadership when things go wrong and times are bad.
Originally published in hardcover by Prima Publishing in 2001.
Includes index.
Keywords: Leadership; Management